2021
DOI: 10.3389/fcvm.2021.733985
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action of MiRNAs and LncRNAs in Extracellular Vesicle in Atherosclerosis

Abstract: Atherosclerosis, a complex chronic inflammatory disease, involves multiple alterations of diverse cells, including endothelial cells (ECs), vascular smooth muscle cells (VSMCs), monocytes, macrophages, dendritic cells (DCs), platelets, and even mesenchymal stem cells (MSCs). Globally, it is a common cause of morbidity as well as mortality. It leads to myocardial infarctions, stroke and disabling peripheral artery disease. Extracellular vesicles (EVs) are a heterogeneous group of cell-derived membranous structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 138 publications
0
16
0
Order By: Relevance
“…The elucidation of the molecular mechanisms regulating the pathological conditions responsible for the development of diseases could provide valuable information that could be useful in developing new methods for the management of these diseases. Many recent studies have shown that miRNAs are promising targets for the diagnosis and treatment of various conditions, including LEAD [ 49 , 50 , 51 , 52 , 53 , 54 ], AAA [ 28 , 55 , 56 , 57 ], and CVD [ 58 , 59 ]. In particular, many investigations were carried out to evaluate the utility of proangiogenic properties of miRNAs in the therapy of peripheral atherosclerosis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The elucidation of the molecular mechanisms regulating the pathological conditions responsible for the development of diseases could provide valuable information that could be useful in developing new methods for the management of these diseases. Many recent studies have shown that miRNAs are promising targets for the diagnosis and treatment of various conditions, including LEAD [ 49 , 50 , 51 , 52 , 53 , 54 ], AAA [ 28 , 55 , 56 , 57 ], and CVD [ 58 , 59 ]. In particular, many investigations were carried out to evaluate the utility of proangiogenic properties of miRNAs in the therapy of peripheral atherosclerosis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“… 131 EVs are secreted by almost all cell types and contain various cargos, such as proteins, nucleic acids, and lipids. 134 Expressions of CD47 on EV membranes offer immune evasion abilities. EVs play vital roles in vascular aging and related diseases.…”
Section: Classification Of Nanoparticlesmentioning
confidence: 99%
“…Cells secrete various protein factors, such as growth factors and cytokines, in response to external stimuli and transduce molecular signals to target cells themselves, locally or throughout the body. In addition to these humoral factors, vesicles comprising biological membranes of phospholipid bilayers (hereinafter referred to as membrane vesicles) are secreted regardless of cell types, such as hematopoietic cells (i.e., platelets, B cells, T cells, dendritic cells, mast cells) and non-hematopoietic cells (i.e., small intestinal epithelial cells, cancer cells, Schwann cells, nerve cells, fat gland cells, sperm, and mammary epithelial cells) [ 31 , 32 , 33 ]. Specific proteins exist on or in the membranes of membrane vesicles.…”
Section: Immune-cell-derived Exosome As An Immune Modulatormentioning
confidence: 99%